EKSPLORASI MATERI ILMU NAHW PADA CHAT-GPT: KOMPARASI PERKEMBANGAN DIGITAL DENGAN KAJIAN TEORITIS PARA PAKAR BAHASA ARAB - Jamil, Husnaini; Astin, Nur Astilah (AL MA'ANY, 2024)
Language as a means of communication will continue to develop along with the development of humans as language users, even with Arabic. If a few years ago Arabic was oriented towards the use of understanding religion, then in this era of society 5.0 Arabic has spread its wings to become a communication language that is actively used by various groups. Learning Arabic is one of the foreign languages that learners are interested in. In this era of society, which cannot be separated from the flow of digitalization on various fronts, the Arabic language has also undergone development, such as the digitization of various Arabic studies. This helps various Artificial Intelligence applications to collect data on the Arabic language and all studies related to it. Like Chat-GPT, In 2024, this application will be able to become one of the references for Arabic learners in finding the studies needed such as the Arabic structure known as Nahw Science. It is hoped that with this digital development, it will be easier for Arabic learners to master Arabic comprehensively and in-depth